PENGARUH PENGGUNAAN AIR SUSU IBU (ASI) DAN POVIDONE IODINE TERHADAP PENYEMBUHAN LUKA PERINEUM PADA IBU POSTPARTUM DI WILAYAH KERJA UPT PUSKESMAS MERAL KABUPATEN KARIMUN - Yuyun Tri Puspita; Prasida Yunita (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
Perineal wound healing that is not good can increase the morbidity rate in postpartum mothers. The purpose of this study was to determine the effect of breastfeeding and Povidone Iodine on perineal wound healing in postpartum mothers who experienced second degree perineal rupture. This research was conducted in January – April 2022, a sample of 20 people who were taken using purposive sampling technique. The study used a quasi-experimental method. Data analysis used Mann Whitney test with 5%. The results showed that the average REEDA scale of perineal wound healing in the breastfeeding intervention group was 0.50, and the average perineal wound healing in the Povidone Iodine intervention group was 2.80. The results of the Mann Whitney test showed a p-value (Asymp. Sig 2 tailed) of 0.004, so the hypothesis was accepted, meaning that there was an effect of the use of breast milk and Povidone Iodine on perineal wound healing in postpartum mothers in the working area of ​​the Tanjung Balai Public Health Center.